2010
DOI: 10.1534/genetics.110.118877
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Survey of Fluoxetine Action on Synaptic Transmission in Caenorhabditis elegans

Abstract: Fluoxetine is one of the most commonly prescribed medications for many behavioral and neurological disorders. Fluoxetine acts primarily as an inhibitor of the serotonin reuptake transporter (SERT) to block the removal of serotonin from the synaptic cleft, thereby enhancing serotonin signals. While the effects of fluoxetine on behavior are firmly established, debate is ongoing whether inhibition of serotonin reuptake is a sufficient explanation for its therapeutic action. Here, we provide evidence of two additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 78 publications
6
52
0
Order By: Relevance
“…1B, Table S1). These results confirm the opposing effects of Mianserin and Fluoxetine on synaptic release of neurotransmitters, with Mianserin increasing and Fluoxetine decreasing the release (Nurrish et al ., 1999; Kullyev et al ., 2010). …”
Section: Resultsmentioning
confidence: 99%
“…1B, Table S1). These results confirm the opposing effects of Mianserin and Fluoxetine on synaptic release of neurotransmitters, with Mianserin increasing and Fluoxetine decreasing the release (Nurrish et al ., 1999; Kullyev et al ., 2010). …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that loss of MOD-5/SERT function increases 5-HT inputs to the neuronal circuit, resulting in behavioral sensitization. Our laboratory has identified that, out of 5 classes of a total of 9 neurons that accumulate 5-HT in C. elegans , a pair of AIM and a single RIH interneurons are 5-HT-absorbing neurons (Kullyev et al, 2010). Here, we report that the MOD-5/SERT function in AIM and RIH neurons controls the response to the experience of food deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine blocks the function of SERT/MOD-5, the serotonin (5HT) reuptake transporter (Keowkase et al 2010; Kullyev et al 2010). As seen in Figure 3, the SWIP response phenotype increased in wild-type animals that were pretreated with fluoxetine but decreased in similarly treated dat-1 (ok157) animals.…”
Section: Resultsmentioning
confidence: 99%